Assessing Alternaria Species and Related Mycotoxin Contamination in Wheat in Algeria: A Food Safety Risk - Meriem Barkahoum Daichi; Mario Masiello; Miriam Haidukowski; Annalisa De Girolamo; Antonio Moretti; Amor Bencheikh; Noureddine Rouag; Stefania Somma (Toxins)
Alternaria species are important fungal pathogens occurring worldwide in wheat, causing both productive and qualitative losses, and posing a toxicological risk to human health due to the production of their mycotoxins in kernels. This study aimed to investigate the occurrence of Alternaria species and their mycotoxins in 48 wheat grain samples collected from the northeast to the southeast of Algeria. Seventy-two representative Alternaria strains were molecularly analyzed using a multi-locus sequence approach and evaluated for their capability to produce mycotoxins under in vitro conditions. Alternaria alternata, representing 42% of the strains, was the dominant species, followed to a lesser extent by species included in the Infectoriae section (26%). In addition, three species not previously reported in Algerian wheat, A. eureka, A. consortialis and A. tellustris, were identified, accounting for 5% of the total strains. Mycotoxin analyses showed high contamination of grains with alternariol monomethyl ether, alternariol and tenuazonic acid, occurring in 75, 69 and 35% of the samples, respectively. Moreover, 41 out of 48 samples showed the co-occurrence of multiple Alternaria mycotoxins. This study provides, for the first, time a clear picture of the occurrence and the distribution of Alternaria species on wheat in Algeria. Finally, the extensive monitoring activities carried out revealed the great biodiversity of Alternaria species able to colonize wheat grains. Moreover, findings on mycotoxin contamination raise concerns about the significant mycotoxigenic risk in Algerian wheat, emphasizing the need for strict monitoring and regulatory measures on Alternaria mycotoxins in food and feed.